AKUNTANSI DALAM PERSPEKTIF BUDAYA JAWA : SEBUAH STUDY ETNOGRAFI PADA PEDAGANG KELILING DI KOTA SEMARANG - Manan, Abdul (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
This study will focus on the actors and accounting users, which is arepresentation of the economic activities of people in the middle to lowersociety in Java society. Javanese culture affects business activities thatbecome the object of research. Javanese culture within Semarang givesdifferent style of accounting practice. Accounting practices that run due tothe influence of Javanese culture will lead to accounting practices that arenatural Java is to practice accounting based on memory and experience, soget used. In addition, the purpose in presenting the information needed bythe internal party has been able to be met well by using a neat andstructured Java culture, although in the simplest form and not inaccordance with accounting in general.